Ứng dụng kỹ thuật viễn thám trong phân loại sử dụng đất và lớp phủ tại Bắc Kạn - Dương, Nguyễn Đình (Vietnam Journal of Earth Sciences, 2003)
Apply remote sensing data analysis for classification of land use/cover in Backan province